A Methodology for Emergent Telecommunication Technology Experiments Based on Virtual Environment and AI Techniques - Benyahi, Ilham (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Advanced telecommunications technologies innovations evolve quickly and are often considered as a main component of critical and emerging applications such as Intelligent Transportation Systems (ITS) and Smart Grid (energy systems). The need of rapid deployment of these technologies requires their testing to assess their performance and if necessary seek appropriate configurations that optimize the QoS (Quality Of Service) of associated applications. Existing simulation tools for testing these technologies remain limited when it comes to appraise their innovations involving additional knowledge. We present in this paper a methodology to design and develop a tool for training and experimentation of technologies innovations such as telecommunication. Our approach is focused on the integration of virtual reality concepts based on object oriented modeling and 3 D techniques for realistic scenarios experiments. We also consider artificial intelligence techniques such as inference mechanisms to enable the integration of new knowledge of the technologies to be tested and their management.